2023
DOI: 10.1021/acsbiomaterials.2c01537
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally Derived Green Carbon Dots from Broccoli Water Extracts: Decreased Toxicity, Enhanced Free-Radical Scavenging, and Anti-Inflammatory Performance

Abstract: Biomass carbon dots (CDs) derived from natural plants possess the advantages of low cost, photostability, and excellent biocompatibility, with potential applications in chemical sensing, bioimaging, and nanomedicine. However, the development of biomass CDs with excellent antioxidant activity and good biocompatibility is still a challenge. Herein, we propose a hypothesis for enhancing the antioxidant capacity of biomass CDs based on precursor optimization, extraction solvent, and other conditions with broccoli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The synthetic C-dots remarkably reduced the expression of IL-6 and TNF-α as the concentration of C-dots increased, compared to the control group [41]. C-dots showed a good ability to regulate NO production by significantly reducing NO − 3 in zebrafish after treatment with C-dots for 2 h [41]. In addition, the synthetic C-dots upregulated the expressions of superoxide dismutase (SOD) and glutathione peroxidase (GPX-4), which, in turn, scavenge excessed ROS and reduce inflammation [41].…”
Section: Anti-inflammatory Activitymentioning
confidence: 87%
See 2 more Smart Citations
“…The synthetic C-dots remarkably reduced the expression of IL-6 and TNF-α as the concentration of C-dots increased, compared to the control group [41]. C-dots showed a good ability to regulate NO production by significantly reducing NO − 3 in zebrafish after treatment with C-dots for 2 h [41]. In addition, the synthetic C-dots upregulated the expressions of superoxide dismutase (SOD) and glutathione peroxidase (GPX-4), which, in turn, scavenge excessed ROS and reduce inflammation [41].…”
Section: Anti-inflammatory Activitymentioning
confidence: 87%
“…In particular, the C-dots can effectively scavenge ROS radicals and downregulate pro-inflammatory mediators (e.g., TNF-α, IL-1α, IL-1β, IL-2, IL-6, IL-8, IL-12, and IFN-γ receptors), which are useful for improving the immune system [10,39,40]. Deng et al (2023) reported the powerful anti-inflammatory activities of C-dots produced from Broccoli water extract using a hydrothermal method (180 • C and 8 h) [41]. The synthetic C-dots remarkably reduced the expression of IL-6 and TNF-α as the concentration of C-dots increased, compared to the control group [41].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 shows simplistic routes towards the formation of hydrogels. In green freeze drying and hydrothermal techniques, water solvent was used [58,59] . Then, ammonium bicarbonate was used to form Ndoped graphene hydrogel with density of 0.034 g cm −3 .…”
Section: Graphene For Sustainable Energymentioning
confidence: 99%
“…The quantum yield of CQDs derived from biomass waste precursors was found to be higher than that from chemical precursors. 21,22 Kundu et al reported the synthesis of uorescent CQDs using biomass precursor rice husk for selective and sensitive detection of Fe 3+ and uoroquinolones. 23 Monte-Filho et al reported highly uorescent CQDs from lemon and onion juices for determination of ribo-avin in multivitamin/mineral supplements.…”
Section: Introductionmentioning
confidence: 99%